Region-Building in the Baltic Region: Legacy of the Inter-War Period and Modern Dynamics - Vladislav Vorotnikov; Alexander Chekov; Ul’yana Yakutova (Международная аналитика, 2019)
The article is devoted to the analysis of historical retrospective and modern dynamics of region-building in the Baltic region. The cultural and historical foundation of regionalization processes in this area was laid over the centuries, although the framework was finally shaped in the 20th century: the Hanseatic League, the first attempts to create regional unions during the interwar period, the “northern cooperation” and the signing of the Helsinki Convention during the Cold War. In the post-bipolar period, the Baltic region continues to maintain its political and socio economic heterogeneity. Today, the key institution of multilateral cooperation uniting all countries of the region is the Council of the Baltic Sea States, whereas, from the EU perspective, the main self-sufficient instrument of regionalization is the EU Strategy for the Baltic Sea Region. At the same time, both formats rely in specific projects implementation on “horizontal actions” and network cooperation on the grass-roots level, which makes regional interaction practical to the greatest possible extent, largely depoliticized and stable in the long run.